Obituary Maroko Myohara - Rüdiger M. Schmelz; Cintia Niva (Soil Organisms, 2024)
We dedicate the contributions of this Newsletter to the memory of Dr Maroko Myohara (Tsukuba, Japan), who passed away suddenly on 24 May 2013, at the age of 61. Dr Maroko Myohara was a developmental biologist at the National Institute of Agrobiological Sciences in Tsukuba, Japan.